PERBANDINGAN PENGETAHUAN IBU TENTANG PEMBERIAN VAKSIN MR (MEASLES RUBELLA) PADA ANAK USIA SEKOLAH - RizkiKhairul rizki (Jurnal Medika Hutama, 2021)
Mothers with high knowledge will provide immunization needs to their children and pay attention to the right time, and vice versa mothers with low knowledge will not know what immunizations should be given to their children. This study aims to compare maternal knowledge about the provision of MR vaccines against the provision of MR (Measles Rubella) vaccines. The design of this study uses a comparative study design. This research was conducted at SDN 77 Pekanbaru in 30 respondents. Data collection in this study uses a questionnaire. Univariate analysis is translated through frequency tables and bivariate analysis using the t test. Based on the results of the study it can be seen the difference in knowledge between mothers who did and did not carry out the MR vaccine. Knowledge of mothers whose children were given the MR vaccine was higher than the average value of 14.40 and mothers who did not do the vaccine averaged only 10. So it can be concluded that there is a difference in maternal knowledge about the provision of MR vaccines to school-age children. Keywords: School age children, Mother's knowledge, MR vaccine